InRES: a digital solution for enhancing research originality and supervision in higher education - Abdullah @Baharum, Mohd Amli; Salim, Azmi; Solat, Naliza; Akmal Said, Zuria; Md Juperi, Nurul Zahidah (2025)
This study introduces the Innovative Research Electronic System (InRES), a digital repository developed to address research topic redundancy and supervision inefficiency in UiTM Pahang's MGT651 course. A quantitative TAM-based study involving 40 students revealed high system acceptance (overall mean = 4.02/5, 74.1% favourable ratings). Perceived Usefulness (PU) emerged as the strongest predictor of Behavioural Intention (β = 0.48, *p* < .001), particularly for enhancing topic originality (rated 4.25/5). Supervisor Impact significantly influenced adoption (β = 0.18; *r* = 0.71 with PU), and students with prior research experience reported 65% higher adoption intention than novices. User feedback prioritized feature enhancements: workflow tools like research timeline trackers (17.5% of suggestions), industry-academia collaboration (12%), and AI-driven topic matching (7.5%). Findings demonstrate that InRES success follows the formula: Adoption = 0.48(PU) + 0.39(Attitude) + 0.18(Supervisor Support), validating its potential to foster originality through accessible research management. Future development should integrate productivity automation and scalability features.